KONTRIBUSI PEMBELAJARAN KEWIRAUSAHAAN TERHADAP PEMBENTUKAN SIKAP KEWIRAUSAHAAN - Rahmat Mamuasi (LPPM Universitas Terbuka, 2010)
Entreprenuerial learning in secondary vocational school aims to produce graduates to overcome the problem of unemployment. This study aimed to identify formation of attitudes and awareness of entrepreneurship towards vocational students after obtaining entrepreneurial training. The effect of entrepreneurial training is measured from the activities of teaching in class, mastery of entrepreneurship, atmosphere / climate of learning, the interest of students on entrepreneurship, and attitudes of students postining. Research with quantitative approach was carried out to 95 student of grade 3 SMK 1 Ternate with background in accounting, office administration marketing, tourism businesses and information technology. Data and information actual through questionnaire prepared in accordance with the variables to be measured. Results showed that a significant contribution of teaching entrepreneurship on the formation of entrepreneurial attitude. This means the higher the level of mastery learning and the better the quality of the learning entrepreneurship atmosphere the greather implications for the change of entrepreneurial attitude. It is recommended that managers SMK supports the effort to create entrepreneurial attitudes through increased teacher competence in the area of entrepreneurship, and empowerment of the role of principal as motivator entrepreneurial behavior in school.